C. S. Lewis: The Question of Multiple Incarnations - Brazier, P. H. (Heythrop journal, 2014)
Formulated by Aquinas, commented on by post-Copernican philosophers and theologians, analysed in depth by C.S. Lewis, and deliberated by some contemporary writers, the question of multiple incarnations either within humanity or amongst extra-terrestrial sentient species is all too intermittently examined: ‘Can the Christ be incarnated more than once in our reality, or somewhere else in the universe, or another reality?’ In this paper, we examine the debate and the conclusions: that is, Lewis’s position within his philosophical theology and his analogical narratives; also, some contemporary philosophers of religion and theologians (Karl Rahner, with Christopher L. Fisher and David Fergusson; Sjoerd L. Bonting and William B. Drees; E.L. Mascall and Brian Hebblethwaite; Oliver Crisp and Keith Ward). How do they relate to Aquinas’s handling of the question and how do they compare with Lewis’s approach based on a theology of the imagination (grounded in Augustine and Alice Meynell)? Can Lewis resolve the argument? Could alien species have witnessed wholly different acts, equally unique, costly to God, and necessary to the process of salvation? Any answer or explanation relates to the function and purpose of the incarnation: the Fall, original sin—therefore, how we define the boundaries, limits, of atonement.